Participatory sustainability approach to value capture-based urban rail financing in India through deliberated stakeholder engagement - Jillella, Satya Sai Kumar; Matan, Annie; Newman, Peter (MDPI, 2014)
Increasingly cities around the world are seeking innovative financial mechanisms to build urban rail transit projects. Land value capture (VC) is a financing mechanism to fund urban rail transit. Often VC mechanisms are viewed only as a financing tool applied in relation to increased land values from the administration and legislation perspectives, without actively involving the community in the process. The lack of such participatory approaches has resulted in the under collection of the true value established. The transit beneficiary community and city tax payers are especially important stakeholders in this process as their willingness to participate is really critical to the overall VC success and transport outcome. This paper introduces a participatory sustainability approach identifying various stakeholder engagement interventions, and a set of appropriate deliberative democracy techniques across the VC life cycle. A four-step “Participatory Strategic Value Capture (PSVC)” framework is proposed offering step by step guidance toward facilitating a meaningful stakeholder dialogue, deliberation and collaboration around the stated engagement interests. The PSVC framework, applied to the proposed Bangalore suburban rail project in India, has demonstrated the importance of stakeholder engagement in order to enable sustainable development community goals and review VC strategies from a win-win perspective.